Do increases in public sector wages affect inflation? - Ozana Nadoveza (Public Sector Economics)
After the pressures from rising energy and food prices subsided, wage increases became the primary risk to inflation. Given concerns that substantial wage growth in the public sector during Croatia’s 2024 election year could create additional inflationary pressures, this paper estimates the potential impact of public sector wage growth on overall inflation using BVAR models. The analysis finds that while the direct impact of 0.15 pp is negligible, there may be a stronger indirect effect. Depending on the assumed (side) effects of public sector wage growth on aggregate demand and the extent of wage spillover to the private sector, the indirect effect of public sector wage growth on inflation could range from 0.34 to 0.88 percentage points. However, considering the double-digit wage growth, it can be concluded that the estimated total contribution of 0.5 to 1 basis points from public sector wage growth is relatively modest.